Unraveling the Complex Role of Zinc, Boron, Chromium, and Selenium in the Pathogenesis of Diabetes Mellitus: A Review - Jawad Musafer , Karar Nadhum; Zulkeflee, Hani Ajrina; Wan Nik, Wan Nor Fazila Hafizan; Ab Rahim, Siti Nadirah; Tuan Ismail, Tuan Salwani (IIUM Medical Journal Malaysia, 2024)
Trace elements are micronutrient components that are only required in small amounts but are critical for the biological functions of many human body tissues. Studies in multiple settings found significant connections between diabetic mellitus (DM) and trace elements caused by disturbances of overlapping cellular metabolic systems. Zinc, boron, chromium, and selenium at either extremely high or low levels could elicit some alteration in cellular metabolism. These lead to the development of DM. The changes include 1) the disturbance in the efficient release of insulin secretory granules, 2) the production of proinflammatory cytokines and oxidative stress state, 3) the failure of insulin signalling pathway, and 4) the reduction of glucose tissue uptake secondary to the downregulation of glucose transporters. Both significantly high and low concentrations have been linked to the development of insulin resistance. Nevertheless, conflicting evidence makes their optimum nutritional levels difficult to establish. For example, lead at a trace concentration may accelerate the development of insulin resistance. The purpose of this review is to emphasise the metabolic role of the 4 trace elements and their influence on the pathogenesis of diabetes when body levels are below optimal. Understanding the consequences of these elements could pave the way for therapeutic possibilities and breakthroughs in personalised DM management.